Isolation and characterization of lytic bacteriophages against Escherichia coli serogroups O1, O2, and O78 - Jamalludeen, Nidham (The Iraqi Journal of Veterinary Medicine, 2012)
The goal of this study was to isolate and characterize a complete set of phages that areactive against Escherichia coliserogroups O1, O2, and O78, the main causative agents ofavian colibacillosis. A mixture of E.coli (O1:K1), (O2:K1), and (O78:K80) used as host toisolate phages from wastewater and fecal samples from poultry processing plants. Elevenphages were isolated, only two of them EC-NJ4 and EC-NJ7 were selected for furthercharacterization. EC-NJ4 and EC-NJ7 had icosaheadral heads, necks and contractile tails,with tail fibers and therefore belonged to Myoviridae, with genome sizes of 67.06 – 68.04 kband they lysed 100% of serotype O1, O2, and O78. The two phages were resistant to pH 5-9,and phage EC-NJ7 was slightly more resistant to acid and alkali environments. It wasconcluded that Phage EC-NJ4 and EC-NJ7 are highly active against O1, O2, and O78colibacillosis strains and it might be suitable candidate for phage therapy.Running title: APEC, Phages, E. coli O1, O2, O78